2009
DOI: 10.1093/glycob/cwp198
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cross-reactive and specific anti-carbohydrate antibodies against lipopolysaccharide from Chlamydophila psittaci

Abstract: Chlamydiae contain a rough-type lipopolysaccharide (LPS) of 3-deoxy-alpha-d-manno-oct-2-ulopyranosonic acid residues (Kdo). Two Kdo trisaccharides, 2.8/2.4- and 2.4/2.4-linked, and a branched 2.4[2.8]2.4-linked Kdo tetrasaccharide occur in Chlamydiaceae. While the 2.8/2.4-linked trisaccharide contains a family-specific epitope, the branched Kdo oligosaccharide occurs only in Chlamydophila psittaci and antibodies against it will be useful in human and veterinarian diagnostics. To overcome the generation of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
(65 reference statements)
2
21
1
Order By: Relevance
“…The affinity of all of the MAbs was in the range of 10 Ϫ7 to 10 Ϫ8 M (Table 1), which is in good agreement with values published for other anti-carbohydrate MAbs (31,32). Importantly, no polyreactive characteristic for any of the MAbs was detected based on lack of binding to unrelated antigens, such as DNA, gelatin, fetuin, and dextran (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…The affinity of all of the MAbs was in the range of 10 Ϫ7 to 10 Ϫ8 M (Table 1), which is in good agreement with values published for other anti-carbohydrate MAbs (31,32). Importantly, no polyreactive characteristic for any of the MAbs was detected based on lack of binding to unrelated antigens, such as DNA, gelatin, fetuin, and dextran (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…This case had a mutational rate lower than the expected experimental error frequency due to Taq DNA polymerase (2 Â 10 5 per base pair per cycle); thus, it was considered as if it did not show intraclonal diversity. Interestingly, no structural similarities between IGs expressed by OAMZL in the present study and the structure of Abs specific for Chlamydiae 27,28 could be demonstrated.…”
Section: Hints For Autoreactivity From the Analysis Of Vh Cdr3 Sequencescontrasting
confidence: 80%
“…26 We also utilized IGHV-D-J sequences of previously reported antiChlamydia Abs. 27,28 To comprehensively identify possible restrictions in the VH CDR3 amino acid composition of the complete data set (OAMZL þ other entities), we used the TEIRESIAS algorithm, 29 a computational tool developed by the Bioinformatics and Pattern Discovery group at the IBM Computational Biology Center, freely available from http://cbcsrv.watson.ibm.com/ download.phtml.html. The parameters used in this analysis are as previously reported.…”
Section: Ig Sequence Analysis and Interpretationmentioning
confidence: 99%
“…This could be perceived as a failure of the immune system to discriminate on the basis of molecular structure or may be seen as a way of tackling different types of invading pathogens simultaneously. Ab cross-reactivities have been described in the past, particularly involving primary Abs where degeneracy appears to be a physiological requirement (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Abs have been shown earlier to achieve binding to diverse Ags through flexible paratope structures involving either partially overlapping residues or achieving Ag-specific structures through induced fit processes (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%